A comparative study on differences in Finnish university students’ motivation between three languages : English, Swedish and an optional language - Rimmi, Eveliina (My University, 2021)
Motivation and language learning has been widely studied before (for example, see Boo, Dörnyei and Ryan, 2015 for an overview of previous L2 motivation research), but comparing motivation between English, Swedish and third (optional) language has not been researched before. In this master’s thesis, the differences in Finnish university students’ motivation amongst three languages (English, Swedish and an optional language) were studied. Given the well-established connection between motivation and performance, another aim of this study was to see if there are differences in motivation, what may be causing differences and if the findings correlate with the ideas presented in Zoltán Dörnyei’s theory “the L2 Motivational Self System”. The participants of the study consisted of university students at a Finnish university. In total, 217 responses were used in the analysis of this thesis. The participants filled an online questionnaire which was split into two sections: questions related to their background information and language learning history whereas the second part focused on questions related to language learning and motivation. In other words, how they perceive language learning as a process, the importance of English, Swedish and their choice of an optional language in the future and personal life. How the participants use and come in contact with the three languages on a daily basis was also examined. In addition to English and Swedish, 11 optional languages were mentioned by the participants. The data were analyzed by using both qualitative and quantitative analysis. The results of the study suggest that students were more motivated in learning English than Swedish and an optional language and this is most likely due to the status of English as a lingua franca. English scored the highest on questions such as “How important role do these languages play in the world in your opinion?” and “How much do you think knowing these languages would help your future career?”. The results also uncovered that students found doing homework in Swedish and optional language equally draining but they were still more motivated to learn their optional language than Swedish. Overall, the students had a more positive view on English than on Swedish and their optional language. The results suggest that even if all languages were considered important, the learners agreed on the importance of English and were therefore most motivated to learn it. In terms of correlation with the concepts presented in Dörnyei’s L2 Motivational Self System, a more detailed study is needed in order to fully comprehend the reasons behind the participants’ levels of motivation and the driving force behind it.